2006
DOI: 10.1007/s00403-006-0705-x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal expression of interleukin-23 in mycosis fungoides/Sézary syndrome lesions

Abstract: Progression of mycosis fungoides (MF) to Sézary syndrome (SS) is accompanied by a shift from a T(H)1 to a T(H)2 cytokine profile. Interleukin (IL)-23 is a novel cytokine that shares a common p40 subunit with the T(H)1 inducer, IL-12. IL-23 induces a third profile, T(H)IL-17, that is dominant in inflammation and autoimmunity. Although IL-23 induces an eczematous-like skin reaction in mice, and is expressed in T(H)1-mediated skin disorders such as psoriasis, it has not been evaluated in MF/SS. To study the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…This result further supports the notion that C-ALCL and LyP (type C) have overlapping histologic features and may be closely related. In agreement with our findings, earlier studies have reported MUM1 expression in 80% to 100% of ALCL [7,8,19]. Unfortunately, these authors did not indicate whether S-ALCL or C-ALCL was included in their studies.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This result further supports the notion that C-ALCL and LyP (type C) have overlapping histologic features and may be closely related. In agreement with our findings, earlier studies have reported MUM1 expression in 80% to 100% of ALCL [7,8,19]. Unfortunately, these authors did not indicate whether S-ALCL or C-ALCL was included in their studies.…”
Section: Discussionsupporting
confidence: 94%
“…Our data confirm and extend the observations reported in the prior studies [4,19,20]. The expression of MUM1 in T-cell lymphoproliferative disorders other than ALCL suggests that this protein may play a role in regulating a much larger spectrum of lymphoid processes than was previously recognized.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Some studies have reported IL-17 mRNA and/or protein expression in situ and ex vivo, whereas others reported its absence, despite the presence of IL-22-producing Th17-like cells. 21,[57][58][59]60 The present findings offer a possible explanation for these opposing results; specifically, that the differences in frequency and severity of skin colonization and infection by SE-producing bacteria between different cohorts of patients and even within a single cohort may explain why IL-17 expression differed between these studies and between patients within a single cohort. 21,57,60 The finding that SEA induces IL-17 expression in nonmalignant primary T cells was not unexpected, given that SEA mediates STAT3 activation in these cells, 77 but it was important because it suggests that both malignant and nonmalignant T cells may contribute to IL-17 expression in vivo.…”
Section: Discussionmentioning
confidence: 67%
“…2b). With regard to this, several studies suggested a skewed Th2 cytokine profile in SS strongly related to the presence of a circulating malignant CD4+ T cell clone with Th2 features [7,8,14,55,56,57]. It is widely known that IgE production is the result of Th2-skewed immune response, but also the presence of CD60 on T cells has been recently associated with functional Th2 profile [58,59].…”
Section: Discussionmentioning
confidence: 99%